2020
DOI: 10.3390/ijerph17249339
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Lower Extremity Ischemia and Its Association with the Frailty Syndrome in Patients with Diabetes

Abstract: Diabetes mellitus is an important risk factor for the development of cardiovascular diseases. Peripheral arterial disease affecting lower limb arteries is one of the clinical manifestations of atherosclerosis. The frailty syndrome (Frailty) is a problem associated with diminution of physiological reserves. The ankle-brachial index is a commonly used tool for diagnosing peripheral arterial disease (PAD). The usefulness of the ankle-brachial index (ABI) is limited in people with diabetes because of calcification… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 113 publications
1
32
0
1
Order By: Relevance
“…It can lead to amputation [13]. The association between PAD and frailty syndrome in patients living with DM has recently been widely described [14].…”
Section: Peripheral Arterial Disease In the Course Of Diabetesmentioning
confidence: 99%
“…It can lead to amputation [13]. The association between PAD and frailty syndrome in patients living with DM has recently been widely described [14].…”
Section: Peripheral Arterial Disease In the Course Of Diabetesmentioning
confidence: 99%
“…In diabetic patients, the BTK arteries are mainly involved with a characteristic symmetrical and multi-segmental stenosis. For this reason, technical success rate of PTA is lower in PAD with diabetes than that in PAD without diabetes [23]. In addition, a study has reported that males were at an increased risk for re-peripheral vascular interventions compared to females [24].…”
Section: Discussionmentioning
confidence: 99%
“…Jakubiak et al also indicated in their literature review that the characteristics of frailty may well affect the clinical course of this condition, treatment efficacy, and complications of chronic lower limb ischaemia [ 35 ]. Moreover, the inflammatory process entailed in the pathogenesis of FS is also encountered in the pathogenesis of atherosclerotic cardiovascular disease and restenosis, following its endovascular treatment, as well as with regard to peripheral arteries [ 36 ].…”
Section: Frailty Syndromementioning
confidence: 99%